2014
DOI: 10.3897/zookeys.408.6612
|View full text |Cite
|
Sign up to set email alerts
|

New tardigrade records for the Baltic states with a description of Minibiotus formosus sp. n. (Eutardigrada, Macrobiotidae)

Abstract: In sixteen moss, lichen and mixed (moss/lichen) samples, collected from Estonia, Latvia and Lithuania, 291 specimens, 48 simplexes, including one exuvium with 6 eggs, and 8 free-laid eggs of eutardigrades were found. In total, 17 species, together with one new to science, were identified (all are new records for the Baltic states): Astatumen bartosi, Diphascon (Adropion) prorsirostre, D. (Diphascon) bullatum, D. (D.) pingue pingue, D. (D.) recamieri, D. (D.) rugosum, Hypsibius convergens, H. dujardini, H. cf. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 61 publications
(102 reference statements)
0
4
0
Order By: Relevance
“…However, based on modern literature, all these records should be considered as dubious and need verification ( Michalczyk et al 2012a , 2012b ). This is now even more necessary due to the discovery in 2014 of two other Milnesium species in Romania ( Ciobanu et al 2014 ): a) Milnesium asiaticum Tumanov, 2006, previously known only from three localities in Kyrgyzstan ( Tumanov 2006 ), Spitsbergen ( Kaczmarek et al 2012b ) and Estonia ( Zawierucha et al 2014 ); and b) Milnesium granulatum (Ramazzotti, 1962) previously known only from three localities in Chile, Italy and USA ( McInnes 1994 ; Bartels et al 2014 ) (see map above).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, based on modern literature, all these records should be considered as dubious and need verification ( Michalczyk et al 2012a , 2012b ). This is now even more necessary due to the discovery in 2014 of two other Milnesium species in Romania ( Ciobanu et al 2014 ): a) Milnesium asiaticum Tumanov, 2006, previously known only from three localities in Kyrgyzstan ( Tumanov 2006 ), Spitsbergen ( Kaczmarek et al 2012b ) and Estonia ( Zawierucha et al 2014 ); and b) Milnesium granulatum (Ramazzotti, 1962) previously known only from three localities in Chile, Italy and USA ( McInnes 1994 ; Bartels et al 2014 ) (see map above).…”
Section: Discussionmentioning
confidence: 99%
“…Since the genus was recently re-described ( Michalczyk et al 2012a , 2012b ) new records and species have been reported from various localities (e.g. Kaczmarek et al 2012a ; Meyer et al 2013 ; Zawierucha et al 2014 ; Ciobanu et al 2014 ). Taking into consideration that some morphological characters were omitted in older records of Milnesium specimens, all such records should be verified ( Michalczyk et al 2012a , 2012b ).…”
Section: Introductionmentioning
confidence: 99%
“…antarcticumTumanov, 2006, only recorded from the Antarctic(Smykla et al 2012), by the maximal length of the buccal tube (≤68 µm in M. alpigenum vs >68 µm in M. antarcticum), a smaller buccal tube standard width (8.6-23.6 µm in M. alpigenum vs 25.9-31.8 µm in M. antarcticum), and by a statistically lower pt of the stylet support insertion point (61.1-70.3, on average 64.9 in M. alpigenum vs 70.0-73.7, on average 71.5 in M. antarcticum; t 38 =16.708, p<0.001).• M. argentinumRoszkowska, Ostrowska & Kaczmarek, 2015, reported from Argentina, by the appearance of cuticle (faint pseudopores visible only with a high quality PCM on the caudal part of the dorsal cuticle in M. alpigenum vs well-visible pseudopores in M. argentinum on the entire dorsum with a standard PCM), and by the lower pt of the primary branches IV (46.9-63.2 in M. alpigenum vs 28.4-36.4 in M. argentinum). • M. asiaticumTumanov, 2006, recorded from Kirghizstan (type locality), China(Beasley & Miller 2007),Estonia(Zawierucha et al 2014) and the Svalbard archipelago (Kaczmarek et al 2012), by a statistically lower pt of primary branches III (39.7-51.7, on average 45.8 in M. alpigenum vs 51.5-58.3, on average 55.3 in M. asiaticum; t 36 =15.385, p<0.001) and by a lower pt of primary branches IV (46.9-63.2 in M. alpigenum vs 63.9-76.0 in M. asiaticum). • M. barbadosense Meyer & Hinton, 2012, only reported from the type locality in Barbados, by a lower pt of the stylet support insertion point (61.1-70.3 in M. alpigenum vs 71.6-82.1 in M. barbadosense) and by a higher pt of the primary branches IV (46.9-63.2 in M. alpigenum vs 28.4-42.2 in M. barbadosense).…”
mentioning
confidence: 99%
“…Species with wide Holarctic distribution [38][39][40]. The original description is uncertain and the species needs a modern redescription [53]. Species new for the Polish fauna.…”
Section: Hypsibius Scabropygusmentioning
confidence: 99%